Management of a mandibular second molar with vertucci type ii (root canal) configuration using fiber-reinforced direct composite: a case report - Veransa, Blofoma Mohentaeses; Rinastiti, Margareta (Padjadjaran Journal of Dentistry, 2024)
Introduction: Vertucci Type II (root canal) configurations in mandibular second molars are rare. These anatomical variations complicate root canal preparation, irrigation, and obturation. The use of fiber-reinforced direct composite contributes to reinforcing teeth post-endodontic treatment, enhancing fracture resistance, and improving the long-term success of restorations, particularly in posterior teeth subjected to significant masticatory forces. This case report aims to present the management of root canal treatment procedures for a mandibular second molar with a Vertucci Type II configuration, and fiber-reinforced composite restorations through carpeting, and wallpapering techniques. Case Report: A 23-year-old female patient presented to the Conservative Dentistry Clinic, RSGM UGM-Prof Soedomo Yogyakarta, for treatment of her lower left second molar. She reported discomfort in the tooth, which had been previously restored two years prior. Six months before the examination, the restoration fractured causing pain. Although the pain has subsided, food debris often accumulated in the resulting cavity. Root canal treatment was performed using single-cone obturation technique with gutta percha and bioceramic sealer to achieve a hermetic sealing. In addition, restoration utilized polyethylene fiber reinforcement applied with wallpapering and carpeting techniques, combined with short fiber reinforced composite (SFRC) for dentin replacement, to enhance structural integrity and fracture resistance. The patient was monitored for one year. Conclusion: Root canal treatment of mandibular second molars with Vertucci type II configuration emphasizes the importance of understanding root canal anatomy, using CBCT for accurate evaluation. Optimal irrigation and hermetic obturation with a single-cone technique with a bioceramic sealer are crucial for treatment success. Post-endodontic restoration with polyethylene fiber-reinforced composite, incorporating short fiber-reinforced composite for dentin replacement, improves fracture resistance and maintains bond integrity.